Parameter extraction for control of a one dimensional movemoent by brain signal - Siti Zuraimi Salleh, 1984-, author; Norlaili Mat Safri, author; Siti Hajar Aminah Ali, author; Regional Student Conference on Research and Development(2008: Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL